Activity-dependent site-specific changes of glutamate receptor composition in vivo. - Schmid, A.; Hallermann, S.; Kittel, R.J.; Khorramshahi, O.; Frölich, A.M.; Quentin, C.; Rasse, T.M.; Mertel, S.; Heckmann, M.; Sigrist, S.J. (Nature Neuroscience, 2008)
The subunit composition of postsynaptic non-NMDA-type glutamate receptors (GluRs) determines the function and trafficking of the receptor. Changes in GluR composition have been implicated in the homeostasis of neuronal excitability and synaptic plasticity underlying learning. Here, we imaged GluRs in vivo during the formation of new postsynaptic densities (PSDs) at Drosophila neuromuscular junctions coexpressing GluRIIA and GluRIIB subunits. GluR composition was independently regulated at directly neighboring PSDs on a submicron scale. Immature PSDs typically had large amounts of GluRIIA and small amounts of GluRIIB. During subsequent PSD maturation, however, the GluRIIA/GluRIIB composition changed and became more balanced. Reducing presynaptic glutamate release increased GluRIIA, but decreased GluRIIB incorporation. Moreover, the maturation of GluR composition correlated in a site-specific manner with the level of Bruchpilot, an active zone protein that is essential for mature glutamate release. Thus, we show that an activity-dependent, site-specific control of GluR composition can contribute to match pre- and postsynaptic assembly.